Online nutrition education: perceived understanding, acceptance, and usability of food and nutrition bytes curriculum for the Expanded Food and Nutrition Education Program - Martin, Lisa J (Kansas State University, 2007)
Nutrition education programs strive to help low-income people make optimal food choices while living on a limited budget. This study addressed perceived understanding, acceptance, and usability of Food and Nutrition Bytes, a set of 12 eight- to eleven-minute online Expanded Food and Nutrition Education Program (EFNEP) lessons. Clients in EFNEP during 2005-2006 were surveyed on internet usage and interest in online nutrition lessons. Lessons were developed and assessed for reading levels using two formulas. Clients and professionals in six Kansas counties completed a Likert scale survey and gave comments after they viewed one online lesson. Fifty-five percent of 75 EFNEP clients who had internet access indicated they were interested in taking nutrition lessons online. The new lessons averaged a 6.64 grade reading level. Two lessons had content that was rated too general to be useful. For the remaining lessons, both groups ranked their perceived understanding, helpfulness of graphics and audio, and usefulness of information at the first or second most-desirable rating. They rated length and amount of information as “Just Right.” The only difference found between the groups was when clients rated one lesson as having a little too much information and professionals rated it as having not quite enough (Mann-Whitney U = 35.0, p = 0.039). Within-sample associations were measured for two lessons. Clients older than 30 years of age found the Grains lesson’s pictures and graphics to be more helpful than did younger clients (Kendall tau-b = 0.593, p = 0.002). White clients evaluated the Cooking lesson as being easier to understand than did non-white clients (Kendall tau-b = -0.477, p = 0.020). The most frequent comments pertained to the importance of portion sizes and appropriate pictures and graphics. Overall, Food and Nutrition Bytes lessons were easy to read, and perceived by both clients and professionals to be easy to understand, helpful and useful, and also optimal in length and amount of information. Despite low numbers of EFNEP clients who had internet access, over half were interested in taking lessons online. Limitations of this study include small samples, convenience samples, subjects’ time constraints, and interviewer bias.
Keywords: Nutrition education; Limited resource; Online learning; Expanded Food and Nutrition Education Program (EFNEP); Family nutrition; Nutrition curriculum; Health Sciences, Nutrition (0570)